KARAKTERISTIK BUAH DAN BIJI KAKAO (Theobroma cacao L) PADA BERBAGAI ALTITUDE DI DATARAN TINGGI SAMOSIR - Sitohang, Nurdin; Benauli, Arkhiadi; Sitanggang, Peby; Zagoto, Fran A. (AGROSUSTAIN, 2023)
The cocoa beans of small holder were usually still low quality, one of it caused by planting location of various altitude in highland. The focus of this research were characteristic of cocoa pod and beans on several altitudes in Samosir highland. The research method were survey as purposive sampling on five altitudes as 815, 930, 1.073, 1.300, and 1.350 m above sea levels (asl). The observed parameters were pod size, pod diametre, pod volume, dry weight of pods, dry weight of kolven, dry weight of beans, bean count per pod, and dry weight per bean at 5 different altitudes, in Samosir highland (>800 m asl) ie: 815, 930, 1.073, 1.300, and 1.350 m asl, with 10 pods (replications) at each altitudes. The results of research showed that: pod size increased, pod diametre increased, pod dry weight increased, dry weight of beans increased, bean count per pod increased, and dry weight each bean increased with the increasing of altitude. The best pods and beans were at altitude of 1.350 m asl, namely fruit length 19.20 cm, fruit dry weight 92.65 g, beans dry weight 47.73 g, number of beans per fruit 40.5 and average weight per bean 1.20 g. The physical characteristics of cocoa pods and beans are still in the normal category.